2019
DOI: 10.1167/tvst.8.4.31
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival HLA-DR Expression and Its Association With Symptoms and Signs in the DREAM Study

Abstract: Purpose Evaluation of dry eye disease (DED) relies on subjective symptoms and signs. We examined HLA-DR expression (HLA-DR%) in conjunctival cells, a minimally invasive biomarker with objective metrics, as an alternative method. Methods Dry Eye Assessment and Management (DREAM) study participants completed the Ocular Surface Disease Index questionnaire. Clinicians evaluated tear volume, tear breakup time, and corneal and conjunctival staining. Conjunctival impression cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…It has been demonstrated that HLA-DR expression by conjunctival cells is increased in patients with uveitis and DED compared with those with vernal keratoconjunctivitis and normal subjects [ 49 ]. Likewise, it is known that high HLA-DR expression in conjunctival epithelial cells associated with high conjunctival staining may identify a subgroup of DED patients prone to epithelial disease that possibly need a different approach from current treatment standards [ 50 ]. These results suggest an involvement of the Th2 system on the ocular surface in uveitis; thus, exploring the ocular surface in uveitis may represent a new way to understand better the immune pathways involved in this complex disease [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that HLA-DR expression by conjunctival cells is increased in patients with uveitis and DED compared with those with vernal keratoconjunctivitis and normal subjects [ 49 ]. Likewise, it is known that high HLA-DR expression in conjunctival epithelial cells associated with high conjunctival staining may identify a subgroup of DED patients prone to epithelial disease that possibly need a different approach from current treatment standards [ 50 ]. These results suggest an involvement of the Th2 system on the ocular surface in uveitis; thus, exploring the ocular surface in uveitis may represent a new way to understand better the immune pathways involved in this complex disease [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Use of a questionnaire may result in misclassifying depression, diluting the strength of associations. However, our prespecified screening cutoff (≤42 in MCS score) has been validated in the US general population and used in various clinical trials to screen for depression . In addition, participants may have been taking medications classified as antidepressants for indications other than clinical depression.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were assayed for percentage HLA-DR positive in total cells, epithelial cells, and white blood cells. Detailed methodology for evaluation of HLA-DR expression has been published …”
Section: Methodsmentioning
confidence: 99%
“…HLA-DR, a surface receptor that is constitutively expressed on antigen-presenting cells, such as dendritic cells, monocytes, B cells, and activated T cells, is one of the most studied inflammatory markers in DED. 13,20 The two previous trials studying the efficacy of v3 on DED that investigated the effect on the expression of HLA-DR showed a decrease in the percentage of conjunctival cells that express HLA-DR or in the intensity of HLA-DR expression. 6,21 In contrast, the present analysis did not show any significant differences between supplementation with v3 versus refined olive oil in patterns of HLA-DR expression in conjunctival surface total, epithelial, or white blood cells.…”
Section: Discussionmentioning
confidence: 99%
“…Details on sample collection, processing, and flow cytometry assessments have been previously published. 13 In short, conjunctival samples were collected separately from both eyes by filter paper-based impression cytology using an established standard operating protocol. 14 Samples were collected from patients at baseline, 6 months, and 12 months.…”
Section: Measurement Of Hla-dr Expressionmentioning
confidence: 99%